1989
DOI: 10.1523/jneurosci.09-08-02919.1989
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative lineage analysis of the origin of frog primary motor and sensory neurons from cleavage stage blastomeres

Abstract: The average number of primary motoneurons and Rohon-Beard neurons that descend from each "identified" blastomere of the 16- and 32-cell stages of the frog Xenopus laevis was determined. The dorsal, animal blastomeres are the major motoneuron progenitors, and the ventral, animal blastomeres are the major Rohon-Beard progenitors. Cells along the midline primarily give rise to only one of these phenotypes, whereas cells along the frontal plane, which separates dorsal from ventral, give rise to both phenotypes. Ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 63 publications
0
25
0
Order By: Relevance
“…3R,T,X). Based on the dorsal/dorsolateral and peripheral positions of the cell bodies, these cells are most likely Rohon-Beard and/or dorsolateral commissural interneurons (Nordlander, 1984;Moody, 1989;Roberts and Sillar, 1990) and are most likely not to be other commissural interneurons, descending interneurons, ascending interneurons or reticulospinal neurons (Soffe et al, 1984;Nordlander et al, 1985;Roberts and Alford, 1986;Roberts et al, 1987;van Mier and ten Donkelaar, 1989). However, positive identification of these flotillin1-positive cells will require characterization by neurotransmitter phenotype, axonal projections, and electrophysiological properties (e.g., Clarke et al, 1984;Gallagher and Moody, 1987;Roberts et al, 1987Roberts et al, , 1988.…”
Section: Resultsmentioning
confidence: 99%
“…3R,T,X). Based on the dorsal/dorsolateral and peripheral positions of the cell bodies, these cells are most likely Rohon-Beard and/or dorsolateral commissural interneurons (Nordlander, 1984;Moody, 1989;Roberts and Sillar, 1990) and are most likely not to be other commissural interneurons, descending interneurons, ascending interneurons or reticulospinal neurons (Soffe et al, 1984;Nordlander et al, 1985;Roberts and Alford, 1986;Roberts et al, 1987;van Mier and ten Donkelaar, 1989). However, positive identification of these flotillin1-positive cells will require characterization by neurotransmitter phenotype, axonal projections, and electrophysiological properties (e.g., Clarke et al, 1984;Gallagher and Moody, 1987;Roberts et al, 1987Roberts et al, , 1988.…”
Section: Resultsmentioning
confidence: 99%
“…1A). This was accomplished by injecting either FITC-dextran (green) or rhodamine-dextran (red) into a single dorsal animal blastomere at the 8-or 16-cell stage and mixing the neural tubes from embryos that were injected with two different fluorophores to prepare dissociated nerve-muscle cocultures (30). Instead of employing electrical stimulation using a glass electrode, which might cause mechanical damages on neurons, we stimulated one of the spinal neurons by local photolysis of caged glutamate (MNI-glutamate; 50 μM) using a multiphoton microscope (31).…”
Section: Activity-dependent Synaptic Competition In Xenopus Nerve-musclementioning
confidence: 99%
“…1F, G), were counted between the otocyst and cloaca (Fig. 1B), as was done to create the original fate map (Moody , 1989).…”
Section: Resultsmentioning
confidence: 99%
“…Primary motoneurons (PMN) innervate the embryonic somitic muscles (Roberts and Clarke, 1982) and likewise are born and begin to differentiate very early in development (Jacobson and Moody, 1984;Chitnis, 2001;Kintner, 2002). Because of their early generation and distinctive morphology, it was possible to create a quantitative lineage map, which showed that stereotypic numbers of both RBN and PMN are produced by identified cleavage stage blastomeres (Moody, 1989). These results suggest that the number of primary neurons that descend from each blastomere might arise because the lineages are determined very early.…”
Section: Introductionmentioning
confidence: 99%